Molecular and Potential Biomarkers in Diagnosis of Cervical Carcinoma: A Review - Likhitha, Kasireddy; Kumar, K.V Nanda; Bindhu, Devarajappa Gari; Charani, Mekala Siva; Priya, Nemali Deepthi; Gowthami, Yaraganti (Asian Pacific Journal of Environment and Cancer, 2024)
Cervical cancer, a potentially preventable disease remains the second most common malignancy in women worldwide. Persistent infection with oncogenic human papillomavirus (HPV) is the main risk factor for cervical cancer and its precursor lesions. It starts in the cell lining of the cervix which includes abnormal cell division and functions. Cytological screening programs using the Pap test have led to a substantial reduction in the incidence of cervical carcinoma. The identification of new biomarkers that allows monitoring of molecular events associated to tumour progression in histological or cytological specimens may improve the detection of lesions with higher risk of progression. In the present article we review on molecular and potential biomarkers that interfere in the pathophysiology of disease and their possible role in screening and diagnosis of cervical cancer.